COLIFORM CONTAMINATION LEVEL OF WASHING WATER AT STREET VENDORS TENT STALLS IN YOGYAKARTA - Amarantini, Charis; Budiarso, Tri Yahya; -, Tri Wahyuni Sekar Sari (BIOMA : Jurnal Ilmiah Biologi, 2024)
Food quality in Indonesia is significantly influenced by street vendors, particularly from a microbiological aspect. The use of unclean washing water in these settings can cause tableware contamination, increasing the risk of food-borne diseases. Therefore, this research aimed to determine the level of coliform contamination in washing water of street vendors. A total of 21 samples were collected from different locations, isolated, and identified morphologically and biochemically. These samples were resuscitated in 1% peptone medium for 12 hours and inoculated on Chromocult Coliform Agar (CCA) medium. Purified coliform colonies were tested morphologically and biochemically to the genus level and confirmed using API 20E KIT reagents. The results showed coliform contamination levels ranging from 5.1 x 105 to 2.7 x 108 CFU/mL, exceeding the quality standard. Confirmation results from testing using API 20E with ID ≥ 95% found bacteria contaminants, including Escherichia coli, Klebsiella pneumoniae subsp. Pneumoniae and Pantoea spp. These results showed the urgent need to recognize the risks associated with tableware contamination at tent stalls. Keywords: API 20E, Coliform, Street Vendors, Washing Water.